WOMEN’S LANGUAGE FEATURES OF A TOP WOMAN CELEBRITY - Nuha, Yasmin Saffana; Yatmikasari, Ika; Permanaludin, Udayani (Jurusan Sastra Indonesia, 2023)
This study aims to examine the style of language that is often used by women. This study discusses the features of women’s language used by Lisa Blackpink in her interview on the Zach Sang Show YouTube channel entitled Lisa Talks Lalisa, Money, Blackpink, & More. Data of this study were analyzed using women’s language features theory by Lakoff (1975). The method used to analyze this research is a qualitative method with data taken from Lisa's interview with Zach Sang which have been transcribed. The results showed that Lisa used nine out of ten women’s language features proposed by Lakoff with a total of 167 data with the following details: 120 lexical hedges/fillers, 20 intensifiers, 5 rising intonations, 5 empty adjectives, 5 hypercorrect grammars, 4 emphatic stress, 4 avoidance of strong swear words, 3 super polite forms, and 1 question tag. Meanwhile, women's language feature that are not spoken by Lisa in her interview was precise color terms.